Transient electronics : pulsed circuit technology - Smith, Paul W. (J. Wiley, 2002)
Passive Pulse Generators are circuits used to generate very high power electrical pulses. Such pulses find application in a wide range of disciplines, including plasma generation, gas laser physics and radar.* Includes two introductory chapters on techniques used to analyse passive pulse generators* Includes worked examplesA valuable reference resource for specialist undergraduates, post graduate students and researchers active in the field og pulsed power and areas where pulsed power is applied, including physicists, engineers and those with an interest in waste and materials processing.